2012
DOI: 10.6117/kmeps.2012.19.2.029
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and Challenges of Cu-to-Cu Wafer Bonding

Abstract: The demand for 3D wafer level integration has been increasing significantly. Although many technical challenges of wafer stacking are still remaining, wafer stacking is a key technology for 3D integration due to a high volume manufacturing, smaller package size, low cost, and no need for known good die. Among several new process techniques Cu-to-Cu wafer bonding is the key process to be optimized for the high density and high performance IC manufacturing. In this study two main challenges for Cu-to-Cu wafer bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 10 publications
0
5
0
1
Order By: Relevance
“…This means that the increase in pattern density might not be able to promote stable metallic contact across the dielectric erosion induced by the CMP process. 25) The previous study 26) also reported that Cu bump after the Cu CMP process was locally bonded at the edge of each bump, producing a very weak bond interface. Therefore, the minimization of both Cu pattern dishing and erosion during CMP process seems to be critical for improving Cu-Cu interconnect direct bonding quality and reliability.…”
Section: Resultsmentioning
confidence: 96%
“…This means that the increase in pattern density might not be able to promote stable metallic contact across the dielectric erosion induced by the CMP process. 25) The previous study 26) also reported that Cu bump after the Cu CMP process was locally bonded at the edge of each bump, producing a very weak bond interface. Therefore, the minimization of both Cu pattern dishing and erosion during CMP process seems to be critical for improving Cu-Cu interconnect direct bonding quality and reliability.…”
Section: Resultsmentioning
confidence: 96%
“…Then, a silicon dioxide (SiO 2 ) dielectric layer 0.3 µm in thickness was formed by dry thermal oxidation at a temperature of 1100 • C. Next, a 1.6 µm-thick layer of silicon nitride (Si 3 N 4 ) was deposited by LPCVD (low pressure chemical vapor deposition) at a temperature of 830 • C. The top electrode was formed by the deposition of in situ n+-doped polysilicon (poly-Si) using LPCVD with a 0.5 µm thickness at 600 • C. The simplified schematic of the manufacturing process is illustrated in Figure 1. It is worth noting that these layers are deposited at varying temperatures, leading to misfit strain at room temperature due to their different CTE, as referenced in [18][19][20][21].…”
Section: Manufacturing Process and Parametrized Samplesmentioning
confidence: 99%
“…However, the mismatch in the coefficient of thermal expansion (CTE) of different applied materials induces the wafer warpage during the fabrication processes. [3][4][5][6][7][8] Large wafer warpage is becoming a critical problem causing many issues such as wafer handling, lithography alignment, device reliability, etc. 9,10) The ultrathin wafers are reported to deform easily due to the increase of the elasticity/reduction of stiffness.…”
Section: Introductionmentioning
confidence: 99%